2020
DOI: 10.1002/jbm.b.34699
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of silk‐based bioink during pre and post 3D bioprinting: A review

Abstract: During past few decades, the demand for the replacement of damaged organs is increasing consistently. This is due to the advancement in tissue engineering, which opens the possibility of regeneration of damaged organs or tissues into functional parts with the help of 3D bioprinting. Bioprinting technology presents an excellent potential to develop complex structures with precise control over cell suspension and structure. A brief description of different types of 3D bioprinting techniques, including inkjetbase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 104 publications
0
28
0
Order By: Relevance
“…However, the viscosity of the SF bioink depends on the type of 3D-bioprinter used. In the case of an extrusion-based printer, a high viscous solution is needed for the extrusion, whereas in the case of an inkjet printer, the viscosity must be low in order to generate droplets [ 82 ].…”
Section: Natural Biomaterialsmentioning
confidence: 99%
“…However, the viscosity of the SF bioink depends on the type of 3D-bioprinter used. In the case of an extrusion-based printer, a high viscous solution is needed for the extrusion, whereas in the case of an inkjet printer, the viscosity must be low in order to generate droplets [ 82 ].…”
Section: Natural Biomaterialsmentioning
confidence: 99%
“…Silk fibers are common in the medical field, most familiar as sutures; however, these two proteins can be separated, and both have unique properties that make them attractive for bioink development. Fibroin is a biocompatible hydrophobic protein with a tailorable rate of biodegradation, high mechanical modulus, and the ability to self-assemble into a hydrogel when dissolved in an aqueous solution [ 132 ]. It forms thermodynamically stable β-sheets which improve mechanical integrity and slow degradation following gelation [ 133 ].…”
Section: Biological Bioinksmentioning
confidence: 99%
“…However, the mechanical strength of DCM and DBM is insufficient because of the loss of cartilage/bone native tissue structure during the homogenization and solubilization process[ 36 , 37 ]. Silk fibroin (SF) is a natural biopolymer that is widely investigated for various 3D bioprinting and tissue engineering applications due to its remarkable mechanical properties, biocompatibility and biodegradation nature[ 38 , 39 ]. In our previous study, we reported the use of a cross-linker-free DCM-SF bioink in printing 3D construct which had similar mechanical properties compared with native cartilage tissue[ 37 ].…”
Section: Introductionmentioning
confidence: 99%